Results of bimanual phacoemulsification with intraocular lens implantation through the micro incision - Synder, Aleksandra; Omulecki, Wojciech; Wilczyński, Michał; Wilczyńska, Olena (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: To evaluate the postoperative results of bimanual, cold phacoemulsification with foldable lens implantation through 1.7 mm incision. Material and methods: Thirty four bimanual cold phacoemulsifications with Acri.Smart® (AcriTec) IOL implantation through 1.7 mm incision were performed in the Department of Ophthalmology, Medical University of Łódź, between March and May 2004. In the group of 34 patients, 24 were women and 10 were men. The mean age of patients was 67 years (range between 42 and 77). Preoperative visual acuity ranged from 0.5/50 to 5/10. Mean visual acuity was 0.3. Preoperative astigmatism ranged from 0.15 to 2.3 diopters (mean 0.7). Preoperatively, nuclear density was estimated according to LOCS III classification. Twenty patients (59%) had l to 3 nuclear density, and 14 (41%) had 4 to 6 nuclear density. All surgeries were performed with Oertli machine using the burst mode with a sleeveless phaco tip. Postoperative examinations were conducted on the 1st and the 7th day, and l month after the surgery. Visual acuity, astigmatism, status of the cornea and IOL centration were evaluated. Results: No intraoperative complications were observed. All 34 patients maintained corneal transparency with no signs of thermal damage around the wound. Visual acuity improved in all cases. Mean visual acuity in 33 patients who had no coexisting ocular diseases l month after surgery was 0.98 and the mean induced astigmatism was 0.2 diopters. In all cases lOLs were very well centred. Conclusions: Bimanual phacoemulsification is a very safe method allowing to minimise corneal incision. Using Acri.Smart IOLs, the induced astigmatism is very small, almost imperceptible to patients.